Analisis Kesulitan Siswa dalam Keterampilan Membaca Siswa Kelas III di SDN 01 Ketapang - Ika Rismawati; Kartinah Kartinah; Asep Ardiyanto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
This study aims to determine students' difficulties in reading skills and factors of reading difficulty in class III SDN 01 Ketapang. This research uses a qualitative approach with descriptive qualitative type. The data subjects in this study were students who had difficulty reading in class III, a total of 6 subjects. Data collection techniques using observation, interviews, triangulation and documentation. Data analysis techniques used are data collection, data reduction, data presentation and conclusion/verification. In class III at SDN 01 Ketapang, the forms of reading difficulties experienced by students were difficulty recognizing consonants such as r, n, v, x, q and were still mistaken in distinguishing the letters "b", "d", "p", q", "m", "n" etc. Another difficulty is not being able to recognize the meaning of words, reducing and adding words in a sentence and ignoring punctuation.